Spinal Mobilization Prevents NGF-Induced Trunk Mechanical Hyperalgesia and Attenuates Expression of CGRP - Reed, William R.; Little, Joshua W.; Lima, Carla R.; Sorge, Robert E.; Yarar-Fisher, Ceren; Eraslan, Mualla; Hurt, Christopher P.; Ness, Timothy J.; Gu, Jianguo G.; Martins, Daniel F.; Li, Peng (Frontiers in Neuroscience, 2020)
Introduction. Low back pain (LBP) is a complex and growing global health problem in need of more effective pain management strategies. Spinal mobilization (SM) is a non-pharmacological approach recommended by most clinical guidelines for LBP, but greater utilization and treatment optimization are hampered by a lack of mechanistic knowledge underlying its hypoalgesic clinical effects. Methods. Groups of female Sprague-Dawley rats received unilateral trunk (L5 vertebral level) injections (50µL) of either vehicle (phosphate-buffer solution, PBS; VEH) or nerve growth factor (NGF; 0.8µM) on Days 0 and 5 with or without daily L5 SM (VEH, NGF, VEH+SM, VEH+SM). Daily passive SM (10min) was delivered by a feedback motor (1.2Hz, 0.9N) from Days 1 to 12. Changes in pain assays were determined for mechanical and thermal reflexive behavior, exploratory behavior (open field events) and spontaneous pain behavior (rat grimace scale). On Day 12, lumbar (L1-L6) dorsal root ganglia (DRG) were harvested bilaterally and calcitonin gene-related peptide (CGRP) positive immunoreactive neurons were quantified from 3 animals (1 DRG tissue section per segmental level) per experimental group. Results. NGF induced bilateral trunk (left P=0.006, right P=0.001) mechanical hyperalgesia and unilateral hindpaw allodynia (P=0.006) compared to the vehicle group by Day 12. Additionally, we found for the first time that NGF animals demonstrated decreased exploratory behaviors (total distance travelled) and increased grimace scale scoring compared to the VEH group. Passive SM prevented this development of local (trunk) mechanical hyperalgesia and distant (hindpaw) allodynia, and normalized grimace scale scores. NGF increased CGRP positive immunoreactive neurons in ipsilateral lumbar DRGs compared to the VEH group ([L1]P=0.02; [L2]P=0.007) and SM effectively negated this increase in pain-related neuropeptide CGRP expression. Conclusion. SM prevents the development of local (trunk) NGF-induced mechanical hyperalgesia and distant (hindpaw) allodynia, in part, through attenuation of CGRP expression in lumbar DRG sensory neurons. NGF decreases rat exploratory behavior and increases spontaneous pain for which passive SM acts to mitigate these pain-related behavioral changes. These initial study findings suggest that beginning daily SM soon after injury onset might act to minimize or prevent the development of LBP by reducing production of pain-related neuropeptides.